2015
DOI: 10.1590/0103-8478cr20150310
|View full text |Cite
|
Sign up to set email alerts
|

Critical-point models to relate yield and disease intensity of the multiple pathosystem in rice leaf spots disease

Abstract: Critical-point models to relate yield and disease intensity of the multiple pathosystem in rice leaf spots disease.Ciência Rural, v.46, n.1, jan, 2016. Critical-point models to relate yield and disease intensity of the multiple pathosystem in rice leaf spots disease tillering and 2012/2013 harvest resulted in R=13.404-92.98I and R=10.685-3.804S. Respectively in each harvest resulted in tillering (R=9.141-103.6I; R=7.605-1.538 and R=8.864-73.91I; R=7.202-77S), panicle initiation (R=9.432-188.5I; R=7.,038-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
0
2
Order By: Relevance
“…The absence of fungicides caused a decrease in vitreous grains with increasing N doses, with the lowest value of 37% at the doses of 120 and 180 kg ha -1 N. When fungicides were applied to the rice plants, higher percentages of milling yield and of whole and vitreous grains were obtained with constant values, regardless of the use of K silicate. Bordin et al (2016), while evaluating the application of fungicides at different phenological stages of irrigated rice cultivars, reported that, when the disease was less severe, there was a higher percentage of milling yield and whole grains.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of fungicides caused a decrease in vitreous grains with increasing N doses, with the lowest value of 37% at the doses of 120 and 180 kg ha -1 N. When fungicides were applied to the rice plants, higher percentages of milling yield and of whole and vitreous grains were obtained with constant values, regardless of the use of K silicate. Bordin et al (2016), while evaluating the application of fungicides at different phenological stages of irrigated rice cultivars, reported that, when the disease was less severe, there was a higher percentage of milling yield and whole grains.…”
Section: Resultsmentioning
confidence: 99%
“…Resultados similares fueron reportados por Aguilar-Anccota et al (2018), los cuales identificaron síntomas de severidad como lesiones necróticas de coloración marrón oscura en panículas y tallos a una edad aproximada de 60 días, así como un incremento de los síntomas en los muestreos posteriores. Se ha reportado que las manchas en hojas causadas por fitopatógenos pueden causar daños por encima del 50 % al disminuir la calidad del grano, existe correlación entre la severidad de las enfermedades foliares y el rendimiento de grano (Bordin et al, 2016b). Otros autores encontraron severidad menor del 4 % en hojas de plantas de arroz durante la etapa vegetativa y que el grado de infección varía dependiendo de las variables utilizadas, sin embargo, la severidad puede aumentar del 4 % hasta el 28 % en la etapa reproductiva ya que la planta es más susceptible al daño por fitopatógenos al utilizar los nutrientes adquiridos para la formación de granos (Cárdenas et al, 2007).…”
Section: Líneas De Arrozunclassified
“…En México, se ha reportado la resistencia y susceptibilidad de estos patógenos. El umbral económico es de 3% (Bordin et al, 2016), sin embargo, se ha registrado incidencias entre 25 y 92% (Barrios et al, 2016), infiriendo que la mayoría de los genotipos nacionales podrían ser afectados significativamente cuando exista un ambiente favorable para el desarrollo de los patógenos.…”
Section: Manchado De Grano De Arroz Causados Por Hongos Fitopatógenosunclassified